Maguirellaria (Caryophyllaceae), a new genus from Dominican Republic - Iamonico, Duilio (Phytotaxa, 2023)
Molecular analyses have shown that Stellaria is a polyphyletic genus and several species are closely related to other genera of Caryophyllaceae. Among the excluded taxa, a group of four species (S. antillana, S. howardii, S. minutifolia, and S. ovata) appear to be not included in the core of Stellaria and are possibly related to the genus Triplateia. Despite this molecular evidence, as well as the morphology of these four species, a formal proposal for a new taxon is still lacking. I here describe the genus Maguirellaria gen. nov., including Maguire’s Stellaria howardii and S. minutifolia. S. antillana and S. ovata, which display a very different morphology in comparison with Maguire’s species, were never considered in the same molecular study; therefore, I prefer to avoid a taxonomic decision for the moment.